Niemiecki model polityki społecznej na tle regulacji Unii Europejskiej - BARAN, PAULINA (Rocznik Integracji Europejskiej, 2012)
The essential objective of the paper is to present the German model of social policy as compared to the social solutions adopted in the European Union. The author analyzes the transformations of social policy, established by virtue of the Treaty on the European Union, The Nice Treaty and Lisbon Treaty, among other documents. The further part of the paper presents the main assumptions of the German model of the welfare state. The author concludes with a suggestion that, at a time of global financial crisis, both the European Union and Germany will need to change their social policies.